Supporting self-regulated learning in a secondary applied mathematics course - Buzza, Dawn; Fitzgerald, Carolyn; Avitzur, Yoad (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
This study examines how one teacher supported low-achieving students’ self-regulated learning (SRL) in the context of a secondary mathematics class. The teacher’s scaffolding provided students with multiple opportunities to use feedback and adapt learning and study strategies. Data compared pre- and postmeasures of metacognitive skills, motivational beliefs, and learning and study behaviours, and examined the effects of directed practice on students’ developing SRL as well as their mathematics achievement. Results suggest the need for more research into the effects of individualized, targeted supports, particularly in assisting students in using metacognitive feedback to adapt learning strategies.